2010
DOI: 10.1111/j.1540-5826.2010.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Teaching Intervention for Classroom Teachers: Helping Struggling Readers in Early Elementary School

Abstract: With the advent of “Response to Intervention” there has been emphasis on preventing reading disabilities. This study examined the effectiveness of a classroom teacher Tier II intervention for struggling readers in kindergarten and first grade called the Targeted Reading Intervention. Three rural schools were randomly assigned to experimental and control conditions, with 8 experimental and 12 control classrooms. Five struggling and five non‐struggling readers were randomly selected from each classroom. With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…In undertaking the current study there were several expectations based on prior research experiences Vernon-Feagans et al, 2010, 2012 with respect to the current research questions. First, there was an expectation that struggling students who received ENRICH would, on average, make sizable gains in reading performance across the school year and would make gains in reading outcomes that were at least comparable to those of their nonstruggling peers.…”
Section: Rationale and Research Questionsmentioning
confidence: 98%
See 1 more Smart Citation
“…In undertaking the current study there were several expectations based on prior research experiences Vernon-Feagans et al, 2010, 2012 with respect to the current research questions. First, there was an expectation that struggling students who received ENRICH would, on average, make sizable gains in reading performance across the school year and would make gains in reading outcomes that were at least comparable to those of their nonstruggling peers.…”
Section: Rationale and Research Questionsmentioning
confidence: 98%
“…The ENRICH intervention was designed for primary grade teachers and their struggling students and was adapted from recent work with rural schools (Amendum, Vernon-Feagans, & Ginsberg, 2011;Vernon-Feagans et al, 2010). ENRICH provides primary grade teachers with ongoing embedded professional development and coaching around an instructional framework of diagnostic strategies designed to promote struggling students' accelerated reading progress.…”
mentioning
confidence: 99%
“…This Tier II intervention focused on individualizing instruction, which has recently been shown to be important in all children's gains in reading (Connor et al, 2009;Morrison, Bachman, & Connor, 2003;Vernon-Feagans, Gallagher, Amendum, et al, 2010). This Tier II intervention focused on individualizing instruction, which has recently been shown to be important in all children's gains in reading (Connor et al, 2009;Morrison, Bachman, & Connor, 2003;Vernon-Feagans, Gallagher, Amendum, et al, 2010).…”
Section: Targeted Reading Intervention (Tri)mentioning
confidence: 99%
“…A majority of the studies did not report information on fidelity of implementation of Tier 1 core reading instruction (see Table 1). Of these, 14 received a 1‐point score (Case et al, 2010; Chambers et al, 2011; Fuchs, Compton, Fuchs, Bryant, & Davis, 2008; Kerins, Trotter, & Schoenbrodt, 2010; Loftus, Coyne, McCoach, Zipoli, & Pullen, 2010; McMaster et al, 2005; Nelson, Vadasy, & Sanders, 2011; Pullen, Tuckwiller, Konold, Maynard, & Coyne, 2010; Schuele et al, 2008; Simmons et al, 2008 , 2011; Tuckwiller, Pullen, & Coyne, 2010; Ukrainetz, Ross, & Harm; 2009; Vernon‐Feagans et al, 2010). Of these, five studies received a second score for reporting fidelity information for supplemental instruction that was provided in addition to the core reading program within Tier 1 (Loftus et al, 2010; McMaster et al, 2005; Pullen et al, 2010; Schuele et al, 2008; Tuckwiller et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The studies reported fidelity far more consistently at Tier 2 (see Table 1). In 17 of the 22 studies, detailed information on fidelity of implementation procedures and related data were provided earning a 3‐point score (Case et al, 2010; Fuchs, Compton, et al, 2008; Kamps et al, 2008; Loftus et al, 2010; Marr et al, 2011; Mathes et al, 2005; McMaster et al, 2005; Murray et al, 2010; Nelson et al, 2011; Pullen et al, 2010; Simmons et al, 2008, 2011; Tuckwiller et al, 2010; Ukrainetz et al, 2009; Vaughn et al, 2009; Vernon‐Feagans et al, 2010; Wanzek & Vaughn, 2008). For example, Case et al monitored protocol compliance in a random selection (25 percent) of audiotaped treatment sessions.…”
Section: Resultsmentioning
confidence: 99%